2008
DOI: 10.1016/j.biocon.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and conservation status of the Yangtze finless porpoise in the Yangtze River, China

Abstract: Endangered Finless porpoise (Neophocaena phocaenoides) Line transect A B S T R A C TThe Yangtze finless porpoise (Neophocaena phocaenoides asiaeorientalis) is endemic to the middle and lower reaches of the Yangtze River, China. It is the only freshwater population of porpoises in the world and is currently listed as Endangered by IUCN. In November and December 2006 we used two boats and line transect methods to survey the entire current range of the population, except for two lakes (Poyang and Dongting). Sight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
183
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 149 publications
(186 citation statements)
references
References 22 publications
1
183
1
1
Order By: Relevance
“…In November and December of 2006, a systematic survey was conducted over the entire current range of the population in the main stem of the Yangtze River (excluding the two lakes, Poyang and Dongting) using a modified standard line-transect survey method pre-designed based on the results of a pilot survey between Wuhan and Yueyang [14] (Figure 1). Experts and researchers from the USA, UK, Germany, Japan, Switzerland, Canada and China joined this international collaborative effort, which utilized both visual and acoustic methods [14,15] . The findings of this extensive survey indicated that the population of the Yangtze finless porpoise in the main stem was approximately 1000 1200; if the populations in the two lakes were included, the entire extant population was approximately 1800.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In November and December of 2006, a systematic survey was conducted over the entire current range of the population in the main stem of the Yangtze River (excluding the two lakes, Poyang and Dongting) using a modified standard line-transect survey method pre-designed based on the results of a pilot survey between Wuhan and Yueyang [14] (Figure 1). Experts and researchers from the USA, UK, Germany, Japan, Switzerland, Canada and China joined this international collaborative effort, which utilized both visual and acoustic methods [14,15] . The findings of this extensive survey indicated that the population of the Yangtze finless porpoise in the main stem was approximately 1000 1200; if the populations in the two lakes were included, the entire extant population was approximately 1800.…”
Section: Reviewmentioning
confidence: 99%
“…These survey results indicate that the current finless porpoise population in the main stem of the river is less than half that estimated from surveys conducted between 1984 and 1991, when the total size of the population in this same section was approximately 2550 [11] . It further implies an annual rate of decline of at least 5% for the entire population in the main stem of the river [14] . The results of the survey also prompted Zhao et al [14] to warn that the distribution of the Yangtze finless is becoming more fragmented, and some gaps in the range may already exist.…”
Section: Reviewmentioning
confidence: 99%
“…The Yangtze finless porpoise, the sole freshwater subspecies of N. phocaenoides, has been listed as an endangered species (EN C2b) in the IUCN Red Data Book since 1996 (Baillie and Groombridge 1996) and has now been listed in the First Order of the National Key Protected Wild Aquatic Animals List in China. Its population has been decreasing annually at a rate of 5% or more (Zhao et al 2008). An exhaustive survey conducted in 2006 by experts from seven countries found that the population of the Yangtze finless porpoise in the main river stem was approximately 1,000∌1,200 individuals, which was less than half of the population size estimated from the surveys from the year 1984 to 1991, and that the distribution is becoming more fragmented (Zhao et al 2008;Wang 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Its population has been decreasing annually at a rate of 5% or more (Zhao et al 2008). An exhaustive survey conducted in 2006 by experts from seven countries found that the population of the Yangtze finless porpoise in the main river stem was approximately 1,000∌1,200 individuals, which was less than half of the population size estimated from the surveys from the year 1984 to 1991, and that the distribution is becoming more fragmented (Zhao et al 2008;Wang 2009). Immediate, proactive, and effective measures must be taken to prevent the Yangtze finless porpoise from following the fate of the Baiji (Wang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The population of the YFP was estimated at $2700 in 1991 [3] but has dropped dramatically in recent years, due to the negative impacts of various human activities, such as illegal fishing, shipping, pollution, water projects, and so forth [4]. At present, the population contains approximately 1800 individuals [5]. Effective protective measures must be rapidly enacted to protect the YFP from extinction.…”
Section: Introductionmentioning
confidence: 99%